2021
DOI: 10.1186/s13065-021-00788-5
|View full text |Cite
|
Sign up to set email alerts
|

A new LC–MS/MS method for multiple residues/contaminants in bovine meat

Abstract: A multi-class and multi-residue/contaminant method for the determination of veterinary drug and pesticide residues and mycotoxins in bovine meat has been developed and validated. The veterinary drug residues/contaminants included antimicrobials, anabolic hormones, lactones, β-agonists, mycotoxins, and pesticides. Isotopic labeled internal standards were included to compensate residual matrix effects. The calibrators used in the method demonstrated linearity with the R2 > 0.98. The decision limit (CCα) value… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The global contamination of food products encompasses various substances, including microorganisms and their nitrates, nitrites, hormones, pesticide residues, antibiotics, metabolites, mycotoxins, heavy metals, dioxins, polychlorinated biphenyls (PCBs), genetically modified organisms (GMOs), toxic pigments and melamine [ 13 ]. Residues of drugs can arise from the therapeutic or prophylactic use of medications in animals raised for food [ 14 ]. The main veterinary drugs that have the potential to contaminate food products include antimicrobial drugs, sedative drugs, nonsteroidal anti-inflammatory drugs (NSAIDs), anticoccidials, growth promoters and anti-helminthic [ 15 ].…”
Section: Regulatory Overview Of Drug Residues In Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…The global contamination of food products encompasses various substances, including microorganisms and their nitrates, nitrites, hormones, pesticide residues, antibiotics, metabolites, mycotoxins, heavy metals, dioxins, polychlorinated biphenyls (PCBs), genetically modified organisms (GMOs), toxic pigments and melamine [ 13 ]. Residues of drugs can arise from the therapeutic or prophylactic use of medications in animals raised for food [ 14 ]. The main veterinary drugs that have the potential to contaminate food products include antimicrobial drugs, sedative drugs, nonsteroidal anti-inflammatory drugs (NSAIDs), anticoccidials, growth promoters and anti-helminthic [ 15 ].…”
Section: Regulatory Overview Of Drug Residues In Foodmentioning
confidence: 99%
“…LC-MS/MS is the most widely used method for detecting drug residues in food. HPLC-MS/MS technology has gained significant interest due to its quick response time, excellent sensitivity, high accuracy, good separation capability, positive/negative ion mode compatibility and broad applicability in analyzing complex samples like swine, bovine, poultry eggs and chicken muscle, aquatic products, meat and milk [ 14 , 83 , 87 , 96 , 96 ]. The high sensitivity and specificity of MS detectors enable the application of generic sample preparation procedures, allowing for the simultaneous extraction of a wide range of residues with different properties.…”
Section: Analysis Of Drug Residues In Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, more sensitive methods for the determination of residues and contaminants in food of animal origin have been developed, but there are few multi-residue and multiclass analytical methods for simultaneous detection of residues of veterinary drugs and other hazards such us pesticides and mycotoxins. Zhan et al, (2013) [ 9 ], developed an LC–MS/MS method for screening for multi-class veterinary drug residues and other contaminants in muscle while Hajrulai-Musliu et al, (2021), reported an LC–MS/MS method for multiple residues and contaminants in bovine meat [ 10 ]. Danezis et al, (2016) [ 11 ], developed a HILIC chromatography-MS/MS method for detection of pesticides, plant hormones, veterinary drugs and mycotoxins in various food matrices while Gómez-Pérez et al, (2015) [ 12 ], published a method for analysis of pesticide and veterinary drug residues in baby food by liquid chromatography coupled to Orbitrap high resolution mass spectrometry, as well as Wei et al, (2015) [ 13 ], who developed multi-residue screening method for analysis of veterinary drugs, their metabolites and pesticides in meat by LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…A low-temperature cleanup method has been developed for these challenging drug residue and contaminant detections in which most lipid components can be successfully separated from extracts. While a wide range of analytes were included, sulfonamides, and several pesticides were not ( 11 , 23 , 27 ).…”
Section: Introductionmentioning
confidence: 99%